2020
DOI: 10.3390/agronomy10060891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bead Composition, PVS Type, and Recovery Medium in Cryopreservation of Bleeding Heart ‘Valentine’—Preliminary Study

Abstract: Bleeding heart (Lamprocapnos spectabilis (L.) Fukuhara) is a valuable ornamental and medicinal perennial. To date, there are few studies focused on cryopreservation of this species, although it could be useful in storage and breeding. This research is aimed at analyzing the effect of bead composition, type of plant vitrification solution (PVS), and the recovery medium of cryopreservation of bleeding heart. Shoot tips of L. spectabilis ‘Valentine’ were used in the study. The explants were precultured on modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, contrasting results are observed in some species where the longer duration of PVS2 and PVS3 treatment are optimum. In Bleeding Heart (Lamprocapnos spectabilis), shoot tips recovered best after 150-min PVS3 treatment [98]. The shoot tips of Golden Paintbrush had a high regrowth at 100 min of treatment with concentrated PVS3 [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, contrasting results are observed in some species where the longer duration of PVS2 and PVS3 treatment are optimum. In Bleeding Heart (Lamprocapnos spectabilis), shoot tips recovered best after 150-min PVS3 treatment [98]. The shoot tips of Golden Paintbrush had a high regrowth at 100 min of treatment with concentrated PVS3 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic seed technology, in addition to fulfilling needs related to micropropagation [ 35 , 36 , 37 , 38 , 39 ], can prove to be an efficient tool for the storage of rare and commercially important species at low temperatures. It has the potential for the medium-term and long-term preservation of plant explants encapsulated in synthetic seeds, without losing viability after immersion in LN when cryopreservation is applied [ 26 , 27 , 28 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that encapsulated shoot tips had a higher tolerance to prolonged dehydration than the "naked" explants, regardless of LN storage (Kulus, 2020b). Supplementing the alginate bead matrix with salts and vitamins from the MS medium and the effect of this factor on plant development were evident (Kulus, 2020a). Encapsulated explants produced longer shoots with larger leaves and higher fresh weights than untreated controls did (Kulus, 2020c).…”
Section: Lamprocapnosmentioning
confidence: 97%
“…Comparative analyses indicated that plant vitrification solution 3 (PVS3) (Nishizawa et al, 1993) was the most effective in the cryopreservation of L. spectabilis, both in terms of explant survival and the quality of the recovered plants (Kulus, 2020a).…”
Section: Lamprocapnosmentioning
confidence: 99%